Pengembangan Website E-Commerce dengan Opencart untuk Promosi Home Industry di Kota Payakumbuh dan Kabupaten Agam - Priyanto, Dimas Putra; Annas, Firdaus; Henra, Raseb (JOVISHE : Journal of Visionary Sharia Economy, 2023)
The development of digital technology opens up great opportunities for home industry players to expand product marketing. However, many businesses face obstacles in utilizing it optimally. This research aims to develop an OpenCart-based e-commerce website to improve home industry promotion in Payakumbuh City and Agam Regency. The research method uses a Research and Development (R&D) approach with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Stages include analyzing the needs of business actors, conceptual design, development using OpenCart, implementation, and evaluation of effectiveness through trials and user feedback. The results showed that the developed website features a product catalog, digital payment, order tracking, and social media integration. This platform increases product visibility, simplifies transactions, and expands the market by 50%. In addition, user testing and feedback showed high satisfaction with the ease of use and effectiveness of this website. This research contributes to encouraging digital transformation for home industry players. By utilizing OpenCart-based e-commerce technology, this research successfully supports local economic growth through increased market access and transaction efficiency. This platform becomes a model for the implementation of digital solutions in the MSME sector, especially in areas with great local economic potential.